Educational Resistance in a Runaway World: Poetic meditations on power and surveillance - Corbett, Michael (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractIt is becoming clear that standard, linear solutions to the problems of resistant children are problematic because they imagine a world of schooling in which place and power do not matter. Poetry can challenge the typically linear, prescriptive, and modernist assumptions that are central to much educational theory and practice. In this article, drawing on original poetry composed in and around schools, I analyze a series of reflective disruptions in the interplay of strategy and tactics in my own teaching career. The broad argument of this paper is that educators ought to recognize, promote and embrace the messiness and complexity of our work rather than retreat into simplifications and technical fixes.